Performance Evaluation of Two Mobile Ad-hoc Network Routing Protocols: Ad- hoc On-Demand Distance Vector, Dynamic Source Routing - Jamilah Alamri, Amnah S. Al-Johani, K. Ibrahim. Ata (International Journal of Advanced Science and Technology, 2020)
A mobile ad-hoc network is a collection of mobile nodes that goatherd to exchange data and information from source to destination. Typically, MANET has no infrastructure, which can call it an infrastructure-less network. The node in the network communicates directly with the neighbor nodes that are already within the wireless range of that node. MANET has several types of routing protocols that can be used to establish links between nodes. These routing protocols are different in their mechanisms, which are AODV and DSR. in this paper. This simulation study carries out two routing protocols to evaluate their performance and quality of service in terms of energy consumption and packet delivery ratio. The comparison study was carried out using the NS2 simulator. The results of the simulations show better performance of DSR over AODV in different scenarios.Keywords: MANET, NS2, AODV, Routing protocols, DSR, QoS